The epidemiology of anemia in pediatric inflammatory bowel disease: Prevalence and associated factors at diagnosis and follow-up and the impact of exclusive enteral nutrition - Gerasimidis, K.; Barclay, A.; Papangelou, A.; Missiou, D.; Buchanan, E.; Tracey, C.; Tayler, R.; Russell, R.; Edwards, Christine; McGrogan, P. (2013)
Background: Anemia is poorly studied in pediatric inflammatory bowel disease. This study explored the epidemiology and associated factors of anemia at diagnosis, after 1 year, and during treatment with exclusive enteral nutrition (EEN). Methods: Three cohorts were included: (1) a representative population of newly diagnosed inflammatory bowel disease children (n = 184); (2) patients currently receiving care with data available at diagnosis (n = 179) and after 1 year (n = 139); and (3) 84 children treated with EEN. Results: At diagnosis, 72% were anemic. Abnormal inflammatory markers were more common in Crohn's disease with severe anemia (severe versus no anemia [%]: raised C-reactive protein; 89% versus 48%; suboptimal albumin; 97% versus 29%; P , 0.002). Anemic children with Crohn's disease had shorter diagnosis delay and lower BMI than nonanemic patients (severe versus mild versus no anemia, median [interquartile range]; diagnosis delay [months]: 3 [3.9] versus 6 [10] versus 8 [18], P , 0.001; BMI z score [SD]: 21.4 [1.4] versus 21.3 [1.5] versus 20.2 [1.4], P = 0.003). Extensive colitis was associated with severe anemia in ulcerative colitis. The proportion of severely anemic patients decreased from 34% to 9% and mild anemia doubled at 1 year. After EEN, severe anemia decreased (32% to 9%; P , 0.001) and the hemoglobin concentration increased by 0.75 g/dL. This was observed only after 8 weeks of treatment. Disease improvement and low hemoglobin at EEN initiation but not weight gain were associated with hemoglobin improvement. Conclusions: Anemia is high at diagnosis and follow-up and should receive more attention from the clinical team; however, the focus should remain suppression of inflammatory process in active disease. © 2013 Crohn's & Colitis Foundation of America, Inc.